Designing with generative systems: a creative-processes-oriented discussion (Estudos em Design, 2022)
The goal of this paper is to provide the theoretical foundations for the study of the creative processes involved in designing with generative systems. To do so, this discussion is sustained by a two-layered literature review. First, creativity, generalist creative processes and creative processes in design are approached. Then, we resort to specific models and concepts of generative design, computational-mediated design processes and computation thinking. In the end, the contribution of this work takes shape as a synthesis of the main aspects learned about the process in question, such as the important role of computational thinking and the implications of a characteristic layer of abstraction that pervades it.